Reflections on statistical modelling: A conversation with Murray Aitkin. (February 2022) - Aitkin, Murray; Hinde, John; Francis, Brian
A virtual interview with Murray Aitkin by Brian Francis and John Hinde, two of the original members of the Centre for Applied Statistics that Murray created at Lancaster University. The talk ranges over Murray's reflections of a career in statistical modelling and the many different collaborations across the world that have been such a significant part of it.